PERINATAL OUTCOMES AND THEIR ASSOCIATION WITH VITAMIN D LEVELS - Turdieva, F.R.; Kayumova , D.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The level of vitamin D in the blood serum of a pregnant woman plays an important role in the physiological course of the gestation period and the birth of healthy offspring. Perinatal outcomes depending on the mother’s vitamin D level have been studied incompletely and are of great practical and scientific interest. The purpose of the study. Determining the relationship between maternal vitamin D levels and neonatal outcomes. Materials and methods. The analysis of the course of pregnancy, childbirth and the assessment of the condition of newborns in 180 women with normal levels, insufficiency and deficiency of vitamin D in the blood serum and umbilical cord blood of newborns was carried out. Results. In children with vitamin D deficiency and deficiency in umbilical cord blood, asphyxia of varying severity was more common, and it was also determined that newborns with low serum cholecalciferol levels have a direct relationship between a low Apgar score and the severity of asphyxia.